(untitled) (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2018)
ينطوي هذا البحث على حقـل الألفاظ الدالة على أعمار الإنسان في لزوميات أبي العلاء المعري ، وبصورة أكثر تحديداً على جمع الألفـاظ المتنوعة الواردة ضمن هذا المجال ، وذكر العدد الذي تكررت ضمنه كل لفظة على حِدَه. وقد قُسِّـم هذا الحقل إلى مجموعات فرعية ، تحددت في أعمار الذكر المتراوحة ما بين الطفولة والشباب والكهولة والشيخوخة مثل: ولـيد ـ طفل ـ غلام ـ فتىً ـ ناشئ ـ شاب ـ رجل ـ كهل ـ أشيب ـ شيخ. وكذلك في أعمار الأنثى المتراوحة أيضاً ما بين المراحل ذاتها التي وجدناها لدى الذكر مثل: وليدة ـ ناهد ـ كاعب ـ فتاة ـ معصر ـ شهلة ـ همة. وبعد الانتهاء من هذا الحقل تمَّت المقارنة ما بين تكرارات هذه الألفاظ وما انطوت عليه من دلالات متنوعة. هذا بالإضافة إلى إظهار العلاقات الدلالية التي وجدت ما بين هذه الألفاظ، وذلك من ترادف وتضاد. وتجدر الإشارة إلى أن هذا الحقل اكتسب أهميته في ديوان اللزوميات من خلال اهتمام الشاعر بصورة واضحة متميزة بحياة الإنسان من بدايتها إلى نهايتها ، نظراً لما تنطوي عليه ـ وفق منظوره ـ من هموم ومتاعب إضافة إلى تشكيلها بكل ما فيها ذلك الجسر الذي سيعبره الإنسان إلى الموت المتوق إليه دائماً لدى الشاعر ما دام سيحقق له غايته المتحددة في الانعتاق إلى الحرية والسكينة . This research underlies the field of words indicating the stages of man’s ages in the obligations of Abi Al Alaa Al Maarri, and more specifically the collection of the various words mentioned within this field. He mentioned the number within which every word was separately repeated. He divided this field into branch groups, talking about the stages of male’s age varying between childhood, youth, middle age and old age, such as: little child, child, lad, youth, junior, young man, man, middle, aged man, grey man and old man . He also talked about the stage of female’s age varying between the same stages which we found in the male, such as: little girl ـ girl in bloom of youth ـ buxom girl ـ girl ـ junior girl ـ young woman and woman . The paper then compares between the repetition of these words and the various indications included in them, in addition to giving prominence to the indicative relations that were found among these words, that is, synonyms and antonyms. It is worth saying here that this field gained its importance in the obligations’ volume through the poet’s interest in a clear and distinctive way in the life of man from its beginning to its end. This is because of what it underlies ـ according to his perspective ـ of cares and troubles it addition to its formation a bridge which man will cross to the death which is always looked forward to by the poet so long as it will fulfill for him the purpose defined in the emancipation to freedom and quietude.